Vulnerability assessment of storage tanks exposed to simultaneous fire and explosion hazards. (February 2023) - Li, Xiaofeng; Chen, Guohua; Amyotte, Paul; Khan, Faisal; Alauddin, Mohammad
Highlights: Vulnerability of storage tanks under simultaneous fire and explosion is addressed. A quantitative method for vulnerability assessment is developed. The effect of pre-fire exposure on the scaled safety distance of tanks is analyzed. The method can be used for rapid quantitative risk assessment of domino effects. Abstract: Storage tanks are vulnerable to the synergistic effect of fire heat radiation and explosion shock wave during domino accidents in hydrocarbon storage tank farms. The available vulnerability analysis model for estimating the damage probability of secondary targets subjected to accident escalation vectors is a critical step for quantitative risk assessment of domino effects. However, due to the complexity of combined loadings, research on the vulnerability assessment of atmospheric storage tanks involved in the synergistic effect of fire and explosion is limited. This study aims to establish a method for quantitative evaluation of the vulnerability of storage tanks exposed to simultaneous fire and explosion hazards. The developed method addresses the coupling effect of high temperature caused by fire and instantaneous strong impulse induced by explosion on the damage probability of atmospheric storage tanks. Application of the proposed method to different cases highlight that pre-fire exposure has significant effects on the damage probability and the scaled safety distance of the tank under subsequent explosion load. The proposed approach can be used for rapid quantitative risk assessment of domino effect involving the synergistic impacts of fire and explosion.